Analysis of the Relevance of Skills and Graduate Performance (Study at the Economic Education Study Program of the Open University) - Sri Sumiyati; Fitra Jaya (Edumaspul: Jurnal Pendidikan, 2023)
Abstract English version, written using Time New Roman-1 1 , italic. Abstract contains research This research aims to 1) find out the whereabouts of graduates (alumni) and establish continuous communication with economic education alumni, 2) identify competency and skill profiles of graduates, 3) find out the relevance of curriculum implementation to labor market needs . This skill and performance relevance analysis study is a qualitative descriptive research, because the problems discussed in this research are not related to numbers, but are related to describing, breaking down and illustrating a problem that is currently occurring. The population of this research is all alumni of economic education study programs from various classes and all companies/institutions/agencies, both state and private, where the alumni work. The sample in this research are alumni who can be contacted face to face or virtually. Data collection was carried out by distributing tracer study questionnaires directly to alumni by: (a) sending questionnaires to the address where the alumni work; (b) distribute questionnaires directly to alumni when there are alumni activities; (c) distribute the tracer study questionnaire link to alumni. Data is analyzed to obtain information from alumni and graduate users. This data was analyzed using descriptive statistics. The data analyzed includes aspects as explained in the questionnaire. The results of the analysis will be used to make improvements to the management system of the Economic Education Study Program.